PEMBUATAN KERAJINAN TANGAN GANTUNGAN TASBIH DAN AKSESORIS CINCIN DI SMPN 1 SERANG BARU - Yulianti, Diva; Mulyadi, Acep; Irham, Irham (Universitas Islam 45 Bekasi, 2024)
The process of making beads and rings from beads is a handicraft that requires high skill and accuracy. Handicrafts in the form of tasbih hangers from beads have become a trend that is in demand by teenagers, because diverse colors, sizes and types of beads can affect the beauty of the product. The purpose of this program is so that the participants always remember Allah SWT, can develop creativity and exercise patience in themselves, and become new ideas for the future. The author uses demonstration and training methods, so that participants can implement them in everyday life. The Program was carried out in Class 8 of SMPN 1 Serang Baru, on Seelasa day, February 27, 2024 at 10.00 WIB, with a target number of 31 students. The results of this activity showed a high enthusiasm of participants in making handicrafts from beads of various shapes and colors. This activity has a positive impact on the community, one of which can build a business to help the economy. The author hopes that after the implementation of this activity, people can apply the knowledge that has been obtained.